2015
DOI: 10.1175/mwr-d-14-00137.1
|View full text |Cite
|
Sign up to set email alerts
|

The More Rain, the Better the Model Performs—The Dependency of Quantitative Precipitation Forecast Skill on Rainfall Amount for Typhoons in Taiwan

Abstract: A strong dependency of model performance in quantitative precipitation forecasts (QPFs) as measured by scores such as the threat score (TS) on rainfall amount (i.e., the better the model performs when there is more rain), is demonstrated through real-time forecasts by the 2.5-km Cloud-Resolving Storm Simulator (CReSS) for 15 typhoons in Taiwan in 2010-12. Implied simply from the positive correlation between rain-area sizes and scores, this dependency is expected to exist in all regions, models, and rainfall re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 83 publications
7
55
1
Order By: Relevance
“…Thus, in such cases, even poorly simulated TC structures can induce realistic rainfall amounts and distribution over the island due to the better representation of topography in high-resolution simulations. This point, which is consistent with recent studies conducted over Taiwan by Wang (2015) and Wang et al (2016), is particularly meaningful for operational forecasts and shows that realistic local rainfall estimates could be obtained despite the partly biased TC life cycle. Conversely, over complex terrain, reliable local estimates of severe weather events require very high-resolution grids so as to properly take into account both orographic effects and finescale processes modulated by the surface conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, in such cases, even poorly simulated TC structures can induce realistic rainfall amounts and distribution over the island due to the better representation of topography in high-resolution simulations. This point, which is consistent with recent studies conducted over Taiwan by Wang (2015) and Wang et al (2016), is particularly meaningful for operational forecasts and shows that realistic local rainfall estimates could be obtained despite the partly biased TC life cycle. Conversely, over complex terrain, reliable local estimates of severe weather events require very high-resolution grids so as to properly take into account both orographic effects and finescale processes modulated by the surface conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Sub-grid-scale processes parameterized include turbulent mixing in the planetary boundary layer, radiation, and surface momentum and energy fluxes (Kondo, 1976;Louis et al, 1981;Segami et al, 1989). With a single domain (no nesting), this model has been used to study a number of heavy rainfall events around Taiwan during the meiyu season (e.g., C.-C. Wang et al, , 2011Wang et al, , 2014a) as well as for real-time forecasts (e.g., Wang et al, 2013Wang et al, , 2016aWang, 2015Wang, , 2016. The CReSS model is open to the research community upon request, and further details can be found in the works referenced above and at http://www.rain.hyarc.…”
Section: The Cloud-resolving Storm Simulator (Cress) and Experimentsmentioning
confidence: 99%
“…There are various communication's channels used in different field of embedded systems recently based on GSM based [34], GPRS [34], WSN network, etc. [19], [20], [21], [22], [23], [24] Climate prediction correctness has been difficult to address. Fault prediction occurs due to climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…representation blunder representation utilizing either 2) stochastic active soul backscatter or 3) stochastically bothered parameterization propensities [21]. Multi-physics and a stochastic active fundamental backscatter arrangement are utilized in a similar system to speak to model instability in a meso-scale troupe conjecture framework utilizing the Weather Investigation and Forecasting model [22].…”
Section: International Journal Of Computer Applications (0975 -8887) mentioning
confidence: 99%